Federalism, oil politics and human security in Nigeria (2015)
This paper investigates how the institution of federalism and the deeply conflictual issue of natural resource exploitation are implicated in the drive for human security in Nigeria. The paper links the literature on geographical determinants of conflicts and violence with the literature on the political determinants of conflict and violence by exploring the institution of federalism as a framework for addressing human security problems in the context of a natural resource driven economy. The paper argues that political institutions are central to achieving human security; therefore, the human security concept must incorporate and account for political institutions for it to address the domestic dimension of the issues. In the Nigerian case, as well as other fragile states, an engagement with federalism as a tool for conflict management, post-conflict reconstruction and guaranteed stability is essential. External human security intervention must take into account the institutional architecture of the state in order for it to promote institution building and sustainability. In such a situation, state institutions and agencies must be recognised and utilized alongside non-state, non-formal organisations in order to avoid the fostering of disengagement or reinforcement of a shadow state which may further undermine state legitimacy and deepen existing distrust between state and citizens.